Street tactics - Kleinschmidt, Frank (School of Architecture, Planning and Geomatics, 2018)
Spatial inequality is the development of public space that selects and benefits certain constituencies over others, with direct effects on how space is used, and by whom. Over time it can contribute to social and political conflict and unrest. In Cape Town, spatial inequality originated largely through apartheid-era strategic planning. Then, as in contemporary Cape Town, this planning typically focused on large-scale infrastructure projects, requiring massive amounts of capital, and was tasked with economic generation in areas that were already yielding returns. Thomas Piketty's definition of inequality as an economic system that favours capital growth over economic growth demonstrates how spatial inequality is essentially the development of spatial capital in areas that already see spatial growth and improvement. Enter tactical urbanism. Mike Lydon, one of its proponents, defines it as a "deliberate, phased approach to instigating change", where local, short-term solutions are found that manage expectations & risk while building social capital. This approach is commonly referred to as "bottom-up", differing from the "top-down" strategic approach of most private and public institutions. Tactical urbanism has the potential to solve spatial inequality by offering a low capital intervention that operates on a small scale with maximum public participation and limited bureaucratic interference. This paper concludes with a discussion on how intervention may exist within Cape Town, specifically in the areas of Woodstock and Salt River. By considering tactical urbanism along with informality, the common characteristics of these two can be utilised to encourage further initiatives, especially ones that accommodate adjacency and counter-gentrification movements.